Study on the harvest of oleaginous microalgae Chlorella sp. by photosynthetic hydrogen mediated auto-flotation for biodiesel production. (15th October 2016) - Feng, Quanzhou; Chen, Ming; Wang, Wenrui; Chang, Sandra; Zhang, Lei; Li, Jihong; Li, Shizhong
Abstract: Harvesting of microalgae biomass is recognized as the bottleneck of algal-based biodiesel production due to its high cost and energy input. In this study, an original harvesting system, the co-flotation using the H2 producing filamentous cyanobacterium Anabaena sp. PCC7120 to concentrate the oleaginous alga Chlorella sp., was presented as an alternative strategy. Different mixing ratios of Anabaena and Chlorella were investigated, and 1: 1 (v/v) was shown to be optimal. In the optimal system, each 100 hydrogen producing cells could float 669 Chlorella cells. The lipid of the floating cells was extracted and analyzed by GC-MS. Results suggested that the co-floated algal cells were rich in saturated fatty acids, higher than Chlorella alone, and thus ideal for biodiesel production. Scale up to 1 L experiments demonstrated the system to have the potential for commercial production. Highlights: Photobiological hydrogen driven co-flotation system was established for harvesting of oleaginous microalgae. Hydrogen production was demonstrated as an essential factor to the system. The harvests system produces hydrogen and lipid simultaneously. The co-floated biomass was proved to be an alternative feedstock for biodiesel production.